Can sleep quality and wellbeing be improved by changing the indoor lighting in the homes of healthy, elderly citizens?. (14th September 2015) - Sander, Birgit; Markvart, Jakob; Kessel, Line; Argyraki, Aikaterini; Johnsen, Kjeld
Abstract : The study investigated the effect of bright blue-enriched versus blue-suppressed indoor light on sleep and wellbeing of healthy participants over 65 years. Twenty-nine participants in 20 private houses in a uniform settlement in Copenhagen were exposed to two light epochs of 3 weeks with blue-enriched (280 lux) and 3 weeks blue-suppressed (240 lux) indoor light or vice versa from 8 to 13 pm in a randomized cross-over design. The first light epoch was in October, the second in November and the two light epochs were separated by one week. Participants were examined at baseline and at the end of each light epoch. The experimental indoor light was well tolerated by the majority of the participants. Sleep duration was 7.44 (95% CI 7.14–7.74) hours during blue-enriched conditions and 7.31 (95% CI 7.01–7.62) hours during blue-suppressed conditions ( p  = 0.289). Neither rest hours, chromatic pupillometry, nor saliva melatonin profile showed significant changes between blue-enriched and blue-suppressed epochs. Baseline Pittsburgh Sleep Quality Index (PSQI) was significantly worse in females; 7.62 (95% CI 5.13–10.0) versus 4.06 (95% CI 2.64–5.49) in males, p  = 0.009. For females, PSQI improved significantly during blue-enriched light exposure ( p  = 0.007); no significant changes were found for males. The subjective grading of indoor light quality doubled from participants habitual indoor light to the bright experimental light, while it was stable between light epochs, although there were clear differences between blue-enriched and blue-suppressed electrical light conditions imposed. Even though the study was carried out in the late autumn at northern latitude, the only significant difference in Actiwatch-measured total blue light exposure was from 8 to 9 am, because contributions from blue-enriched, bright indoor light were superseded by contributions from daylight.